Serious Pervasive Games - Coelho, António; Rodrigues, Rui; Nóbrega, Rui; Jacob, João; Morgado, Leonel; Cardoso, Pedro; van Zeller, Maria; Santos, Liliana; Sousa, A. Augusto (Frontiers in Computer Science, 2020)
Serious Pervasive Games extend the “magic circle” to the players’ surrounding environment. The blend of both physical and fictive game worlds provides a push in player engagement and promotes situated learning approaches. Space and time, as well as social context, acquire a more meaningful impact on the gameplay. From pervasive learning towards science communication with location-based games, this article presents case studies that exemplify their benefits and related problems. Pervasive learning can be defined as “learning at the speed of need through formal, informal and social learning modalities”. The BEACONING project aims to contextualize the teaching and learning process, connecting it with problem-based game mechanics within STEM. The main goal of this project is to provide the missing connection between STEM subjects and real-world interactions and applications. The pedagogical foundation is based on problem-based learning, in which active learning is in the center, and learners have to work with different tools and resources in order to solve problems (quests). Teachers create, facilitate and assess pervasive and gamified learning activities (missions). Furthermore, these quests are gamified in order to provide non-linear game plots. In a second case study, we demonstrate and evaluate how natural heritage can benefit from pervasive games. For example, in a natural park, a set of location-based games has been developed in order to provide enhanced experiences, as well as additional information about some species that are more difficult to observe or that are seasonal. Throughout the development of this project, we have encountered and identified several problems, of different natures, present in pervasive games. As a solution to some of these problems, we propose adaptivity, customizing the gameplay to the users’ profile and context.